2010
DOI: 10.1203/pdr.0b013e3181f74940
|View full text |Cite
|
Sign up to set email alerts
|

N-3 Long-Chain Polyunsaturated Fatty Acids Prevent Excessive Fat Deposition in Adulthood in a Mouse Model of Postnatal Nutritional Programming

Abstract: This study investigates whether improved quality of nutrients during early postnatal life has effects on adult metabolic profile and body composition in a murine model of nutritional programming. Male offspring of C57Bl/6j dams received a diet containing 21% energy (En%) as fat of either 100% vegetable oils [control (CTRL)] or 80% vegetable oils/20% tuna fish oil [rich in n-3 long-chain polyunsaturated fatty acids (n-3 LCP)] from postnatal day (PN) 2 to 42. Subsequently, mice of both experimental groups were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 40 publications
2
41
2
Order By: Relevance
“…In addition, n3 long-chain polyunsaturated fatty acid supplementation during pregnancy and lactation reduced BW of adult rat offspring on a standard chow by 5% (28). In accordance, we have shown previously that 5% n3 long-chain polyunsaturated fatty acids in the postnatal diet of mice lowers adult FM by 28% upon 56 d of WSD feeding (18). The magnitude of this nutritional programming effect on adult FM closely resembles that of our present study, which investigated a postnatal diet with distinct physical and compositional lipid properties without any significant change in FA composition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, n3 long-chain polyunsaturated fatty acid supplementation during pregnancy and lactation reduced BW of adult rat offspring on a standard chow by 5% (28). In accordance, we have shown previously that 5% n3 long-chain polyunsaturated fatty acids in the postnatal diet of mice lowers adult FM by 28% upon 56 d of WSD feeding (18). The magnitude of this nutritional programming effect on adult FM closely resembles that of our present study, which investigated a postnatal diet with distinct physical and compositional lipid properties without any significant change in FA composition.…”
Section: Discussionsupporting
confidence: 92%
“…To test this hypothesis, we developed a concept IMF with lipid droplets with physical properties similar to those in HM, i.e., larger in size and coated with PLs (Nuturis; Danone Research, Paris, France). We compared this concept IMF with a control IMF in a mouse model of nutritional programming (18). A diet containing either control or concept IMF was provided…”
mentioning
confidence: 99%
“…These observations showed that ARA via metabolism of LA was a key determinant in fat mass and globally underlined that LA/LNA ratios during perinatal period could have important programming effect on body composition (Ailhaud et al, 2006). Further proofs of evidence of lipids being involved in programming other functions were obtained in 2010 in animal models (rodents) by two research groups (Innis et al, 2010;Oosting et al, 2010). These results were obtained on non-dairy lipids but paved the way for further investigations on 'dairy lipid structure and programming' conducted just after by Oosting et al (2011Oosting et al ( , 2012Oosting et al ( , 2014.…”
Section: Introductionmentioning
confidence: 90%
“…At the same time, Oosting et al (2010) investigating further Ailhaud's group hypothesis (Ailhaud et al, 2006), established still in a rodent model, that n-3 LCPUFA-rich neonatal diet programmed adult body composition (reduction of 30% fat accumulation during western style diet challenge) and metabolic homeostasis. Healthier plasma lipid profile, plasma glucose parameters and less adipocytes hypertrophy were observed in the group of mice that had received the n-3 enriched diet during neonatal period.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation